Remarks on the genera Balssia Kemp, 1922 and Acanthonyx Latreille, 1828 in the Azores, and first record of Calappa tuerkayana Pastore, 1995 (Crustacea, Decapoda) in the Atlantic Ocean. - Udekem d'Acoz, Cédric d' (2008)
The morphology of the Azorean populations of the caridean shrimp Balssia gasti (Balss, 1921) is here examined. This species, which was not previously recorded from the Azores, proves to have a spectacular variability in the development of dorsal carapace processes. The variability of the Azorean majid crabs of the genus Acanthonyx is also studied. Comparison with Mediterranean Acanthonyx lunulatus (Risso, 1816) show some morphological differences but also an important overlap in characters. The Azorean Acanthonyx are therefore identified as A. lunulatus. The Azorean Acanthonyx also show some similarities with the poorly known species Acanthonyx brevifrons A. Milne-Edwards, 1869 from the Cape Verde Islands, a species of uncertain validity. Calappa tuerkayana Pastore, 1995, a crab recently described from the Mediterranean Sea, is recorded for the first time in the Atlantic Ocean: a unique male has been found off Pico island. This specimen is here described and illustrated.